Training and its impact on the efficiency of workers in the institution and industry - kerma, boualem; atika, hararia (Journal of Social Sciences and Humanities, 2021)
It’s evident that the human resource’s formation becomes one of the strategies factors most important in any society. We speak about formation’s roles in making the workers more able in their function’s, thanks to the enorme competence received but the formation. It’s used to ameliorate the workers performance, in objective to have a good production, and best presentation